2005
DOI: 10.1103/physrevd.71.014032
|View full text |Cite
|
Sign up to set email alerts
|

Volume dependence of the pion mass in the quark-meson model

Abstract: We consider the quark-meson-model in a finite three-dimensional volume using the Schwinger proper-time renormalization group. We derive and solve the flow equations for finite volume in local potential approximation. In order to break chiral symmetry in the finite volume, we introduce a small current quark mass. The corresponding effective meson potential breaks chiral O(4) symmetry explicitly, depending on σ and π fields separately. We calculate the volume dependence of the pion mass and of the pion decay con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(124 citation statements)
references
References 33 publications
7
117
0
Order By: Relevance
“…This will be explored in future work. We wish to note, however, that negative values for R[M π ] have also been observed in the quark meson model for unequal spatial and temporal box lengths, see [16,17] for details.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…This will be explored in future work. We wish to note, however, that negative values for R[M π ] have also been observed in the quark meson model for unequal spatial and temporal box lengths, see [16,17] for details.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The choice of boundary conditions affects the behavior of the pion mass in finite volume [20] as well as the chiral phase transition temperature [21]. For periodic spatial boundary conditions, the presence of a quark zero-momentum mode leads to an enhancement of the chiral condensate.…”
Section: Introductionmentioning
confidence: 99%
“…In many lattice QCD simulations, periodic boundary conditions are chosen in order to minimize finite-volume effects. In a model calculation, we have indeed found that that this choice minimizes finite-volume effects [20].…”
Section: Introductionmentioning
confidence: 99%
“…This behavior can be indeed observed in our RG analysis once order-parameter fluctuations are taken into account, cf. also previous RG studies of finite-volume effects in QCD low-energy models [43][44][45][46].…”
Section: Beyond Mean-field and The Role Of Fluctuations In A Finimentioning
confidence: 99%
“…For our analysis we employ a functional renormalization group (FRG) approach and apply techniques similar to those used for the analysis of finite-volume effects in QCD low-energy models [43][44][45][46][47]. For our purposes, such an approach is advantageous since it allows us to investigate the "transition" between the finite system and its continuum limit.…”
Section: Introductionmentioning
confidence: 99%